2015
DOI: 10.1017/s135561771500106x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exercise Improves Prefrontal Cortex but not Hippocampal Function in Healthy Adults

Abstract: The effects of acute aerobic exercise on cognitive functions in humans have been the subject of much investigation; however, these studies are limited by several factors, including a lack of randomized controlled designs, focus on only a single cognitive function, and testing during or shortly after exercise. Using a randomized controlled design, the present study asked how a single bout of aerobic exercise affects a range of frontal- and medial temporal lobe-dependent cognitive functions and how long these ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 69 publications
5
78
2
7
Order By: Relevance
“…Of note, four studies did not report intensities for their interventions [47, 52, 53, 55], and after reviewing each intervention more closely, two of which were yoga centered [52, 53], all four were subsequently reported as “low” intensity. Additionally, only one study indicated a “vigorous” PA intensity [57], which was changed to join the eight studies with “moderate to vigorous” PA intensity. We found intensity was a significant moderator ( Q  = 7.399, p  = 0.025) between low ( n  = 5), moderate ( n  = 3), and moderate to vigorous ( n  = 9) PA intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, four studies did not report intensities for their interventions [47, 52, 53, 55], and after reviewing each intervention more closely, two of which were yoga centered [52, 53], all four were subsequently reported as “low” intensity. Additionally, only one study indicated a “vigorous” PA intensity [57], which was changed to join the eight studies with “moderate to vigorous” PA intensity. We found intensity was a significant moderator ( Q  = 7.399, p  = 0.025) between low ( n  = 5), moderate ( n  = 3), and moderate to vigorous ( n  = 9) PA intensities.…”
Section: Resultsmentioning
confidence: 99%
“…See also Figure S3 for raw performance scores. See also Table S2. effects of exercise conducted immediately after acquisition, suggesting that experimental parameters such as task, type of learning, type of stimulus material, and subject population could be important for the net effect of exercise on memory retention [12,14,33,34]. It remains a challenge for future research to determine the specific parameters that modulate the impact of exercise on memory.…”
Section: Figure 2 Memory Retention-test 2/test 1 Performancementioning
confidence: 99%
“…Most of this work, understandably, has been conducted among older adults (see review articles (Bherer et al ., ; Carvalho et al ., ; Gajewski & Falkenstein, ; Lu et al ., )). Emerging research evaluating the effects of exercise on memory among younger, healthy adults has demonstrated evidence supporting functional strengthening and proliferation of neural connections and regional brain activation in areas specifically subserving memory performance (Miles & Hardman, ; Libkuman et al ., ; Covassin et al ., ; Sibley & Beilock, ; Labban & Etnier, ; Berman et al ., ; Gothe et al ., ; Nanda et al ., ; Basso et al ., ; Loprinzi & Kane, ; McNerney & Radvansky, ; Bantoft et al ., ; Hwang et al ., ; Crush & Loprinzi, ; Loprinzi et al ., ). The emergence of this line of inquiry in this young adult population is warranted given that memory has been shown to start to decline among young adults in their 20s (Salthouse, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the population (fewer studies in young adults) and potential temporal effects of exercise on memory, three additional gaps in the literature include the exercise stimulus, memory type, and memory follow‐up period. With regard to the exercise stimulus, and despite animal work demonstrating that high‐intensity exercise is effective in increasing post‐synaptic excitatory activity (Swiatkiewicz et al ., ) and long‐term memory (Wang & Wang, ), the majority of research in the young adult population (Miles & Hardman, ; Libkuman et al ., ; Covassin et al ., ; Sibley & Beilock, ; Labban & Etnier, ; Berman et al ., ; Gothe et al ., ; Nanda et al ., ; Basso et al ., ; Loprinzi & Kane, ; McNerney & Radvansky, ; Bantoft et al ., ; Hwang et al ., ) has employed moderate‐intensity exercise protocols. Regarding memory type, all of the studies in the young adult population (Miles & Hardman, ; Libkuman et al ., ; Covassin et al ., ; Sibley & Beilock, ; Labban & Etnier, ; Berman et al ., ; Gothe et al ., ; Nanda et al ., ; Basso et al ., ; Loprinzi & Kane, ; McNerney & Radvansky, ; Bantoft et al ., ; Hwang et al ., ) have examined either retrospective‐related episodic memory, recognition memory, logical memory, working memory, long‐term memory, visuospatial memory, or verbal memory.…”
Section: Introductionmentioning
confidence: 99%